A LOW-DOSE PROTECTIVE EFFECT OF PHYCOCYANIN ON THE TOXICITY OF DELTAMETHRIN TO VITAL ORGANS IN RATS: IN VIVO STUDY - A. C., Bouzar1, Benali2, Y.; A., . Bitam1 (university of eloued جامعة الوادي, 2020)
The study highlights the histopathological alterations of the liver, kidney and heart of female rats exposed to a low dose of deltamethrin (DLM), the potential hepatoprotective, nephroprotective and cardioprotective effects of phycocyanin. Twenty-four (24) female Albino Wistar rats divided into four groups recognised as follows: Control rats received a standard diet (C). Group (PC) treated with a standard diet enriched with 3.6 ± 0.1 mg of phycocyanin per kg of granules. Group (DLM) treated with a standard diet combined with DLM in water at a concentration of 1.28 mg per kg body weight per day. The remaining group (DLM / PC) was processed by the combination of the DLM and PC scheme. The toxicity of DLM was revealed by transaminase analysis and histological observation. The association (DLM + PC) revealed a protective effect of phycocyanin as illustrated by the reduction of the concentration of serum AST and the important decrease of lesions in the tissues studied. Therefore, it shows that PC has a protective action against the toxic effects of DLM.
artical
Keywords: Pyrethroid; phycocyanin; hepatoprotective; nephroprotective; cardioprotective.